Punjab’s Wetlands as Inland Analogues of Marine Ecosystems: Status, Stressors and CommunityLed Conservation. - Atul Khajuria (International Journal of Marine Life, 2026)
Aquatic and wetland ecosystems in Punjab, India, represent ecologically significant yet increasingly degraded socioecological systems embedded within an intensively managed agrarian landscape. Despite their recognised importance, existing studies largely treat these systems using conventional freshwater ecological frameworks, with limited integration of microbiologically mediated processes and broader ecosystem theories. A key research gap, therefore, lies in the lack of interdisciplinary approaches that can holistically interpret wetland structure, function, and governance across spatial scales, particularly by incorporating microbial drivers of nutrient cycling and element transformation. This review applies marine ecosystem frameworks—spatial zonation, trophic organisation, biogeochemical cycling, and connectivity—to reinterpret Punjab’s wetlands as inland analogues of coastal systems. A narrative–systematic approach was used, integrating literature from Scopus, Web of Science, and Google Scholar. Six Ramsar wetlands (Harike, Ropar, Kanjli, Nangal, Keshopur Miani, and Beas) were analysed. Results show strong ecological parallels with coastal lagoons, particularly in nutrient cycling and habitat connectivity mediated by microbial processes. However, these systems face stressors such as nutrient enrichment, heavy metal contamination, hydrological changes, invasive species, and land-use shifts, leading to eutrophication and biodiversity loss. Reservoir wetlands are more vulnerable, while community-managed systems show greater resilience. Bioindicators and microbial indices effectively assess ecosystem health. A “Large Aquatic Ecosystem” framework is proposed for sustainable wetland management.
Keywords: Keywords: Inland wetlands; microbial biogeochemistry; nutrient cycling; trophic structure; zonation patterns